The Effects of Cyberloafing on Organizational Commitment: The Role of Emotional Exhaustion and Job Overload - Muafi Muafi (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2023)
Technological developments and the increasing use of smartphones have significantly changed individual behavior in organizations. This era has created cyberloafing behavior at work. This study explores the antecedents and determinants of cyberloafing behavior by examining the role of emotional exhaustion and job overload and their effect on organizational commitment. The respondents of this study were 300 star-rated hotel employees in the Province of Special Region of Yogyakarta selected by purposive sampling. The data collected by distributing questionnaires were then processed using the Structural Equation Modelling method using Smart PLS. The results showed that emotional exhaustion increased employee cyberloafing behavior, while job overload decreased cyberloafing behavior. Cyberloafing was also found to hurt organizational commitment. Finally, cyberloafing was proven to mediate the effect of emotional exhaustion and job overload on organizational commitment. In conclusion, these findings suggest that creating a healthy and attractive work environment balanced with the right allocation of tasks will likely lead to reduced cyberloafing.